Issues in the Definition and Valuation of Sustainable Buildings in Lagos, Nigeria - Oyalowo, Basirat Ashabi; Babawale, G K (Unilag Journal of Humanities, 2019)
The purpose of this paper is to contribute to the academic discourse on the incorporation of sustainability into property valuation practice. The study assesses the criteria guiding the conceptualisation of sustainable buildings as found in academic literature and proposes a holistic, lifecycle based conceptualisation of sustainable buildings; which can then be localised as necessary. The elements from the conceptualisation are then developed into sustainability features of a hypothetical property, which is then used as the basis for the quantitative aspect of the study. The study is based on a survey of practising estate surveyors and valuers in forty two estate firms in Lagos; selected with the use of cluster sampling and surveyed with a semi-structured questionnaire. Data was analysed using descriptive statistics. Analysis revealed that although the investment approach was acknowledged to be the most appropriate method of sustainable building valuation, the most readily available data inputs were for the cost method of valuation. Given the state of market maturity, this implies that the cost method presently remains the most expedient method of valuation of such properties. It was also found that respondent valuers possess limited experience in the valuation of buildings with core environmental features. While there are perceptions of capital and rental value increases attributable to sustainable buildings, there is limited expertise on how to account for sustainability features, and these could affect value judgments. It is recommended that as the sustainable property sub-market grows, specific training for valuers on sustainability, continuous professional development, systematic information gathering and sharing within the market must be strategically carried out to ensure the appropriate capture of the impact of sustainability on property value.